Chemical composition, antioxidant, and antimicrobial properties of Mentha subtomentella: in sight in vitro and in silico analysis - Brahmi, Fatima; Bentouhami, Nour Eddine; Rbah, Youssef; Elbouzidi, Amine; Mokhtari, Ouafae; Salamatullah, Ahmad Mohammad; Ibenmoussa, Samir; Bourhia, Mohammed; Addi, Mohamed; Asehraou, Abdeslam; Legssyer, Bouchra (Frontiers in Chemistry, 2024)
Our research focused on assessing essential oils (MSEO) and aqueous extracts (MSAE) derived from M. subtomentella leaves, with a primary focus on evaluating their properties. From 1 kg of leaves, we successfully obtained 18 mL of essential oil. Upon conducting GC/MS analysis, we identified eleven compounds within the oil, collectively accounting for 100% of the constituents identified. Notably, the predominant compounds in the leaf oil were p-Menth-48) -en-3-one (50.48%), 9-Ethylbicyclo (3.3.1) nonan-9-ol (10.04%) (E)-3,3-Dimethyl-delta-1, alpha-cyclohexaneacetaldehyde (8.53%), and D-Limonene (7.22%). Furthermore, utilizing HPLC/DAD, we explored the phenolic profile of MSAE, extracted through decoction. This analysis revealed the presence of fifty-eight compounds, with five major components collectively constituting 61% of the total compounds identified, rosmarinic acid as the major one. We evaluated the antimicrobial effectiveness of the MSEO against ten different strains, observing its notable efficacy against A. Niger (MIC = 0.09%), P. digitatum (MIC = 0.5%), and G. candidum (MIC = 1%). However, the essential oil demonstrated comparatively lower efficacy against bacteria than fungi. In contrast, the MSAE did not exhibit any antimicrobial activity against the tested strains. Regarding antioxidant activity, the aqueous extract displayed a significantly higher antioxidant capacity than the essential oil, which exhibited relatively lower antioxidant activity. The IC50 values were determined to be 0.04 ± 0.01 mg/mL, 0.17 ± 0.01 mg/mL, and 13% ± 0.01% (V/V), for ascorbic acid MSAE and MSEO, respectively. We used a computational method called molecular docking to investigate how certain plant compounds affect antioxidant, antibacterial, and antifungal activities. This involved analyzing the interactions between these compounds and specific protein targets known for their roles in these activities.